2014
DOI: 10.3109/00498254.2014.981609
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cerebral CYP2D alters tramadol metabolism in the brain: interactions of tramadol with propranolol and nicotine

Abstract: 1. Cytochrome P450 2D (CYP2D) protein is widely expressed across brain regions in human and rodents. We investigated the interactions between tramadol, a clinically used analgesic, and brain CYP2D regulators, by establishing concentration-time curves of tramadol and O-desmethyltramadol (M1) in rat cerebrospinal fluid (CSF) and plasma, as well as by analyzing the analgesia-time course of tramadol. 2. Propranolol (20 μg, intracerebroventricular injection), CYP2D inhibitor, prolonged the elimination t1/2 of trama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Propranolol attenuated the increases in tramadol‐induced analgesia by orchiectomy, indicated by lower AUC (0–60 min) (31%, P < 0.001) and AUC (0–180 min) levels (56%, P < 0.001) (Figure ). This is consistent with our previous finding that propranolol attenuated the enhancement of tramadol‐induced analgesia following chronic nicotine treatment due to the decreases in nicotine‐induced M1 production via brain CYP2D (Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Propranolol attenuated the increases in tramadol‐induced analgesia by orchiectomy, indicated by lower AUC (0–60 min) (31%, P < 0.001) and AUC (0–180 min) levels (56%, P < 0.001) (Figure ). This is consistent with our previous finding that propranolol attenuated the enhancement of tramadol‐induced analgesia following chronic nicotine treatment due to the decreases in nicotine‐induced M1 production via brain CYP2D (Wang et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Propranolol, given i.c.v., attenuated the increase in the production of M1 from tramadol within the brain induced by orchiectomy, which is consistent with previous findings that propranolol decreases the metabolism of codeine and tramadol in rat brain via the inhibition of brain CYP2D (Zhou et al ., ; Wang et al ., ). The inhibition of brain CYP2D by propranolol attenuated the enhancement of tramadol‐induced analgesia induced by orchiectomy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…While mRNA studies have shown that CYP2D4 is the predominant isoform in the rat brain (Funae et al, 2003;Hiroi et al, 1998), other isoforms of CYP2D, such as 2D1 or 2D5, have also been detected in the rat brain, albeit at much lower concentrations (Miksys et al, 2000;Mizuno et al, 2003;Wyss et al, 1995). Studies with rats and monkeys have shown that the concentration and pharmacological response of analgesics and antipsychotics are better correlated with the variability in CYP2D enzyme activity in the brain, as opposed to the hepatic CYP2D (McMillan & Tyndale, 2015;Wang et al, 2015;Zhou et al, 2013). Additionally, induction of brain CYP2D can be independent of its expression in the liver (Mann et al, 2008;Yue et al, 2008).…”
Section: Introductionmentioning
confidence: 99%